Construction of women`s all-around speed skating event performance prediction model and competition strategy analysis based on machine learning algorithms - Liu, M.; Chen, Y.; Guo, Z.; Zhou, K.; Zhou, L.; Liu, H.; Bao, D.; Zhou, J. (Frontiers in Psychology, 2022)
Introduction: Accurately predicting the competitive performance of elite athletes is an essential prerequisite for formulating competitive strategies. Women`s all-around speed skating event consists of four individual subevents, and the competition system is complex and challenging to make accurate predictions on their performance.